Phytosociological description of the dwarf mountain pine shrub community (Amelanchiero ovalis-Pinetum mugo) in the valleys of the Slovenian Alps - Dakskobler, Igor (Acta silvae et ligni, 2023)
We have expanded our knowledge of the localities, sites and distribution of the Amelanchiero ovalis-Pinetum mugo association in the Slovenian Alps. Based on phytocenological analyses, the shrub association belonging to the forest vegetation type Alpine mountain pine scrub was divided into two subassociations: peucedanetosum oreoselini and hylocomiadelphetosum triquetri. We also described four variants within the latter association.
Keywords: fitocenologija; Krajinski park Topla; Natura 2000; phytosociology; Pinus mugo; sinsistematika; Slovenia; Slovenija; synsystematics; Topla Landscape Park; Triglav National Park; Triglavski narodni park